PATHOLOGICAL PHYSIOLOGY OF CORONARY HEART DISEASE - Rakhimova Gulnoz Shamsiyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. Ischemic heart disease is a disease that develops as a result of absolute insufficiency of the coronary circulation and manifests itself by myocardial damage of varying degrees. Insufficiency of the coronary circulation is a pathological condition characterized by the inability of the coronary vessels to provide blood supply to the heart in accordance with its energy needs. In other words, there is a discrepancy between the energy needs of the heart and the delivery of oxygen and nutrients by the coronary vessels. Insufficiency of the coronary circulation can be relative and absolute.